The Impact of Local: Exploring Availability and Location on Food Buying Decisions - Laura M. Gorham; Joy N. Rumble; Jessica Holt (Journal of Applied Communications, 2015)
The term “local food ” is a buzzword in the food industry for consumers. However, when consumers make food-purchasing decisions, do they look for the specif ic growing locations and consider the seasonality of the product? In this study, researchers used focus groups to determine the impact growing location and months of availability have on consumers’ purchasing decisions in order to identify effective communication strategies when communicating about local food. The theoretical framework of framing and cognitive dissonance informed this study. The findings from this research indicated consumers defined local food as grown in a certain area, state, or region. Additionally, results indicated consumers make food-buying decisions based on personal preference, versatility, health benef its, preparation, and seasonal cooking. Overall, consumers’ decisions to buy produce were not impacted by growing season, but rather by their preference for a specific product. Participants noted most produce is available year round nationally. The researchers recommend communicators focus on developing message strategies framed toward the purchasing attributes identified by the participants instead of growing location and availability. Future research should continue to examine the impact of different frames on consumer food-purchasing decisions and how consumers perceive specific message frames.
Keywords: Local food; buying decisions; qualitative; focus groups; framing; cognitive dissonance